Biocontrol of Penicillium digitatum with secondary metabolites of endophytic fungi in mandarin fruits - León-Ttacca, Betsabe; Arestegui-Cantoral, Yasmin; Tarula-Gutierrez, Brandy; Orellana-Cornejo, Cesar; Luis-Vilcamiza, Jorge; Flores-Pelaez, Pedro (Agronomía Mesoamericana, 2024)
Introduction. “Green mold,” caused by Penicillium digitatum is one of the phytosanitary issues that limits citrus production. For its control, synthetic fungicides are used, which have lost effectiveness due to resistance developed by the fungus. An alternative is the use of endophytic fungi with biocontrol action. Objective. To evaluate the effect of secondary metabolites (SM) from endophytic fungi (EF) on the mycelial inhibition of Penicillium digitatum and the effectiveness of disease control in mandarin fruits (Citrus reticulata) post-harvest. Materials and methods. The study was conducted in 2022, using a completely randomized experimental design in the Plant Health Laboratory at the Universidad Nacional de Cañete (UNDC), Lima, Peru. For the antibiosis test, secondary metabolites were extracted from ten strains of EF from the genera Trichoderma sp., Fusarium sp., and Aspergillus sp., where mycelial inhibition of the pathogen (%) was evaluated. SMs were sprayed at 15 % (v/v) concentration on mandarin fruits that were disinfected and inoculated with the pathogen by spraying (1x 105 CFU/cc). Additionally, a commercial biocontrol, a vegetable oil, and a fungicide were used. After 6 and 9 days, disease incidence (%) and severity index (0, 1, 2, 3) were evaluated. Results. Secondary metabolites from strains the HEA-111 (Aspergillus), HEA-109 (Fusarium), and HSA-1 (Trichoderma) showed the highest mycelial inhibition with 95.05 %, 87.51 %, and 47.47 %, respectively. In mandarin fruits treated with SMs from strains HEA-109 and HSA-1, there was a control of 80 % and 55 %, respectively. Conclusions. SMs from EF were effective in inhibiting the mycelial growth of P. digitatum and reduces disease progression in mandarin fruits post-harvest.